THE EFFECTIVENESS OF 5E LEARNING CYCLE MODEL TOWARD MATHEMATICS LEARNING OUTCOMES OF STUDENT GRADE VII AT SMP MUHAMMADIYAH 2 KALASAN - Indah Fitria Noor Arifin; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was done because there are many students who are less active and less enthusiastic in learning process. Students are reluctant to ask about the material they have not understood that the learning outcomes obtained are less optimal. This research aims to determine the effectiveness of mathematics learning by using Learning Cycle 5E model toward learning outcomes of students' mathematics of class VII SMP Muhammadiyah 2 Kalasan district Sleman in Even Semester in Academic Year 2015/2016. This was control group posttest only. The population in this research were students class VII SMP Muhammadiyah 2 Kalasan district Sleman. Samples were taken using random sampling techniques derived class VII A as an experimental class and class VII C as the control class. The data collection is done with test method. Testing instrument using validity and reliability. Data were analyzed using analysis prerequisite test including normality test with the formula Chi-square, homogeneity test by test Bartlett, and hypothesis testing with t-test. Based on calculations by the significant level  5% and the degrees of freedom 58, we concluded that: (1) There is differences in learning outcomes of students learning math using Learning Cycle 5E Instructional Model with learning using direct Learning Model. This is indicated by the results of the first test of the hypothesis that  2,406  >  = 2,002 (2) learning using Learning Cycle 5E Instructional Model is more effective than learning using direct Learning Model. It is shown on the second hypothesis that the test results  2,406 >  = 1,671.